"Una copita amigo": Ethnic Mexicans, consumer culture, and the American marketplace. Issue 4 (December 2016) - Gaytán, Marie
Abstract In this article, I trace the introduction and evolution of tequila in the American marketplace as a means of exploring how race and ethnicity, commodities, and consumption operate in the organization of everyday life. Analyzing the content of English and Spanish documents from the mid-nineteenth through the early twentieth centuries, I argue that divergent meanings were ascribed to tequila in ways that both solidified notions of racial difference and allowed for the positive affirmation of identity. Anglos focused on its medicinal and, later, toxic properties, while ethnic Mexicans steadily incorporated it into their ritual practices and affirmatively expressed their identity through its consumption. Despite, or perhaps because of, tequila's freighted meaning as an emblem of Mexican deviance in Anglo society, ethnic Mexicans valued and used tequila as a culturally significant symbol ofmexicanidad . By focusing on tequila's commercial history, I illustrate how ethnic Mexicans nourished traditions, both long-standing and newly formulated. Tequila, and the codes of its consumption, provided a platform for resistance and the creative expression of solidarity.